(untitled) (Damascus University Journal for legal sciences, 2024)
This study dealt with an issue that has become so prevalent in our time that it has been pervaded by affliction, which is the phenomenon of loathing that some people tolerated, and were ignorant of its rulings, and neglected some of its modern forms. Hence, the money of al-Ghulul is not limited to the ghoul alone, but may be transferred from one hand to another by one of the ways of transferring ownership. Hence, the research was divided into two sections, the first section dealt with the definition of the words of the rule “the change of the cause of ownership is the place of the change of the self”, and its general meaning and its legal rooting. Some contemporary images of the issue, ending with a statement of the effect of the rule of “change of cause of ownership” on Al-Ghulul.